Reframing Cancer Education Through Mental Health Literacy: Integrating the Psychosocial Dimension of Care - Bernardo Flôr-Rodrigues; Olga Carvalho; Louis J. Koizia; Benjamin H. L. Harris; Pieter Vandekerckhove (Journal of Cancer Education, 2026)

Disentangling effects of protection on seabed organic carbon and biodiversity in a rare highly protected mud-dominated MPA - Benjamin Harris; Tara Williams; Mara Fischer; Torsa Sengupta; Ceri Lewis; Adam Porter; Julie Hawkins; Zoe Roseby; Callum Roberts (Estuarine, Coastal and Shelf Science, 2026)

Diet of juvenile skipjack herring Alosa chrysochloris : Ontogenetic shifts, predator–prey size ratios and mouth gape allometry - Joshua P. Egan; Peter J. Hundt; Neil P. Rude; Jason A. DeBoer; Benjamin J. Lubinski; Kristopher A. Maxson; Levi E. Solomon; Andrya L. Whitten Harris; Andrew M. Simons (Journal of Fish Biology, 2026)
The skipjack herring Alosa chrysochloris inhabits Gulf of Mexico drainages, primarily the Mississippi River Basin, and estuarine environments in the Gulf of Mexico. The trophic ecology of the skipjack herring is poorly understood, therefore we quantified the length, mouth gape and gut contents of juvenile skipjack herring from the Mississippi River (fish n = 6), Illinois River (fish n = 181) and Ohio River (fish n = 255) and tested for changes in diets and predator–prey size ratios during ontogeny. We identified statistically significant changes in prey type consumption during ontogeny. Aquatic insects dominated the diets of skipjack herring 40 mm SL were primarily composed of fishes. The most prevalent fish species consumed by skipjack herring were invasive bigheaded carps Hypophthalmichthys spp. and preliminary evidence indicated that inter‐annual variation in the consumption of bigheaded carps was driven by variation in juvenile bigheaded carp abundance. Additional research is needed to determine if the enhancement of native skipjack herring populations could be used as a tool to limit bigheaded carp population sizes. Skipjack herring SL and mouth gape were both significantly positively correlated with maximum, median and minimum sizes of prey consumed. There were allometric changes in the mouth gape of juvenile skipjack herring, with the ratio of mouth gape to SL increasing until ~80 mm SL, then gradually declining. Maximum mouth gape to SL ratios corresponded to substantial increases in the consumption of fishes, indicating that mouth gape allometry may facilitate the ontogenetic transition to piscivory in the skipjack herring. This study improves our understanding of skipjack herring ecology and provides data that can be incorporated into future ecological and evolutionary research, such as the development of food web models.

Learning with Patients: Reflections on Cancer, Complexity and Innovation in Education - Pieter Vandekerckhove; Louis J. Koizia; Benjamin H. L. Harris (Journal of Cancer Education, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Development of a powerful PlexSeq™ SNP panel for grandparentage studies for snake river fall Chinook salmon - Matthew R. Campbell; Audrey C. Harris; Zachary L. Robinson; Rebekah L. Horn; Shawn R. Narum; Benjamin Kaufman; Kristen Richards; Thomas A. Delomas (Conservation Genetics Resources, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Ecological impacts of floating offshore wind on marine mammals and associated trophic interactions: current evidence and knowledge gaps - Caitlin B. Harris; Steven Benjamins; Beth Scott; Benjamin J. Williamson (Marine Pollution Bulletin, 2025)

Triple oxygen isotopes in eggshell carbonate as a proxy of late Cenozoic CO2 and primary productivity - Vincent J. Hare; Drake A. Yarian; J. Tyler Faith; Chris Harris; Julia A. Lee-Thorp; Benjamin H. Passey; Kathryn G. Sokolowski; Loïc Ségalen (Geochimica et Cosmochimica Acta, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Rapid Evolution in Action: Environmental Filtering Supports Coral Adaptation to a Hot, Acidic, and Deoxygenated Extreme Habitat - Carlos Leiva; Gergely Torda; Chengran Zhou; Yunrui Pan; Jess Harris; Xueyan Xiang; Shangjin Tan; Wei Tian; Benjamin Hume; David J. Miller; Qiye Li; Guojie Zhang; et al. (Global Change Biology, 2025)
The semienclosed Bouraké lagoon in New Caledonia is a natural system that enables observation of evolution in action with respect to stress tolerance in marine organisms, a topic directly relevant to understanding the consequences of global climate change. Corals inhabiting the Bouraké lagoon endure extreme conditions of elevated temperature (> 33°C), acidification (7.2 pH units), and deoxygenation (2.28 mg O2 L‐1), which fluctuate with the tide due to the lagoon's geomorphology. To investigate the underlying bases of the apparent stress tolerance of these corals, we combined whole genome resequencing of the coral host and ITS2 metabarcoding of the photosymbionts from 90 Acropora tenuis colonies from three localities along the steep environmental gradient from Bouraké to two nearby control reefs. Our results highlight the importance of coral flexibility to associate with different photosymbionts in facilitating stress tolerance of the holobiont; but, perhaps more significantly, strong selective effects were detected at specific loci in the host genome. Fifty‐seven genes contained SNPs highly associated with the extreme environment of Bouraké and were enriched in functions related to sphingolipid metabolism. Within these genes, the conserved sensor of noxious stimuli TRPA1 and the ABCC4 transporter stood out due to the high number of environmentally selected SNPs that they contained. Protein 3D structure predictions suggest that a single‐point mutation causes the rotation of the main regulatory domain of TRPA1, which may be behind this case of natural selection through environmental filtering. While the corals of the Bouraké lagoon provide a striking example of rapid adaptation to extreme conditions, overall, our results highlight the need to preserve the current standing genetic variation of coral populations to safeguard their adaptive potential to ongoing rapid environmental change.

Liver structure and function in yellowtail kingfish, Seriola lalandi, in response to alternative oils in feed - Benjamin H. Crowe; James O. Harris; Todd J. McWhorter; Matthew S. Bansemer; David A.J. Stone (Aquaculture, 2025)

An investigation of an outbreak of Salmonella Typhimurium infections linked to cantaloupe – United States, 2022 - Sharon Seelman Federman; Erin Jenkins; Cullen Wilson; Arturo DeLaGarza; Colin Schwensohn; Benjamin Schneider; Johnson Nsubuga; Robert Literman; Allison Wellman; Brooke M. Whitney; Rebecca L. Bell; Kerri Harris-Garner; et al. (Food Control, 2024)

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Emplacement and flow dynamics in a small volcanic dyke swarm: The example of Mount Calanna (Etna, Italy) - Rasia Shajahan; Andrew Harris; Sara Mana; Eugenio Nicotra; Claudio Robustelli Test; Benjamin Van Wyk de Vries; Elena Zanella (Journal of Volcanology and Geothermal Research, 2024)

Global status, impacts, and management of rocky temperate mesophotic ecosystems - James J. Bell; Valerio Micaroni; Benjamin Harris; Francesca Strano; Manon Broadribb; Alice Rogers (Conservation Biology, 2024)
The ecology and function of rocky temperate mesophotic ecosystems (TMEs) remain poorly understood globally despite their widespread distribution. They typically occur at 20–150 m (the limit of photosynthesis), and on rocky substratum they support rich benthic communities and mobile fauna. We determined the distribution of rocky TMEs, their conservation status, and their most characteristic biological groups. Rocky TMEs were dominated by algae, turf‐invertebrate matrices (

Emplacement of monogenetic lava flows on eroded terrain, Part II: The case of the Artière valley (Grave Noire, France) - Andrew Harris; Benjamin Latutrie; Benjamin Van Wyk de Vries; Élodie Saubin; Marine Foucher; Lucia Gurioli; Elena Zanella; Etienne Médard; François Nauret (Journal of Volcanology and Geothermal Research, 2023)

Emplacement of lava flows on eroded terrain, part I: The case of the Tiretaine valley (Chaîne des Puys, France) - Benjamin Latutrie; Andrew Harris; Benjamin Van Wyk de Vries; Lucia Gurioli; Etienne Médard (Journal of Volcanology and Geothermal Research, 2023)

Cover Image - Rachel N. Hofer; Allen Lin; Benjamin C. House; Christopher N. Purvis; Bradley J. Harris; Steven J. K. Symes; David K. Giles (Journal of Fish Diseases, 2023)

Exogenous polyunsaturated fatty acids ( PUFAs ) influence permeability, antimicrobial peptide resistance, biofilm formation and membrane phospholipid structure in an A‐layer and non‐A ‐layer strain of Aeromonas salmonicida - Rachel N. Hofer; Allen Lin; Benjamin C. House; Christopher N. Purvis; Bradley J. Harris; Steven J. K. Symes; David K. Giles (Journal of Fish Diseases, 2023)
Aeromonas salmonicida is a Gram‐negative bacterium that can infect a wide host range of fish populations, including salmonids and non‐salmonids as well as freshwater and marine life. Some strains of A. salmonicida cause the disease furunculosis, which can cause lethargy, intestinal inflammation, ulcers, haemorrhaging and death. The infection is spread through fish‐to‐fish contact, and the presence of infection can have devastating effects on cultivated fish populations. The purpose of this study was to explore the ability of non‐A‐layer and A‐layer A. salmonicida strains to incorporate polyunsaturated fatty acids (PUFAs) into their lipid profile and test the phenotypic effects thereof. Lipids were extracted from PUFA‐exposed cultures and analysed for lipid modification by thin‐layer chromatography and ultraperformance liquid chromatography‐mass spectrometry, showing A. salmonicida , regardless of A‐layer, capable of incorporating all seven of the PUFAs studied. Phenotypic effects were determined through the use of assays that tested for biofilm formation, membrane permeability and cyclic peptide susceptibility. Temperature‐dependent effects on biofilm formation were observed, and PUFA exposure showed significant ( p

Obesity: a perfect storm for carcinogenesis - Benjamin H. L. Harris; Valentine M. Macaulay; David A. Harris; Paul Klenerman; Fredrik Karpe; Simon R. Lord; Adrian L. Harris; Francesca M. Buffa (Cancer and Metastasis Reviews, 2022)
Obesity-related cancers account for 40% of the cancer cases observed in the USA and obesity is overtaking smoking as the most widespread modifiable risk factor for carcinogenesis. Here, we use the hallmarks of cancer framework to delineate how obesity might influence the carcinogenic hallmarks in somatic cells. We discuss the effects of obesity on (a) sustaining proliferative signaling; (b) evading growth suppressors; (c) resisting cell death; (d) enabling replicative immortality; (e) inducing angiogenesis; (f) activating invasion and metastasis; (g) reprogramming energy metabolism; and (h) avoiding immune destruction, together with its effects on genome instability and tumour-promoting inflammation. We present the current understanding and controversies in this evolving field, and highlight some areas in need of further cross-disciplinary focus. For instance, the relative importance of the many potentially causative obesity-related factors is unclear for each type of malignancy. Even within a single tumour type, it is currently unknown whether one obesity-related factor consistently plays a predominant role, or if this varies between patients or, even in a single patient with time. Clarifying how the hallmarks are affected by obesity may lead to novel prevention and treatment strategies for the increasingly obese population.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Individual migration strategy fidelity but no habitat specialization in two congeneric seabirds - Benjamin Merkel; Sébastien Descamps; Nigel G. Yoccoz; David Grémillet; Francis Daunt; Kjell E. Erikstad; Aleksey V. Ezhov; Mike P. Harris; Maria Gavrilo; Svein‐Håkon Lorentsen; Tone K. Reiertsen; Harald Steen; et al. (Journal of Biogeography, 2021)
Aim In migratory species, individuals often use fixed and individual‐specific migration strategies, which we term individual migration strategy fidelity (IMSF). Our goal was to test if guillemots have flexible or fixed individual migration strategies (i.e. IMSF), if this behaviour is consistent across large parts of the genus’ range and if they were philopatric to geographical sites or a habitat feature. Location North Atlantic. Taxon Uria spp. Methods We quantified consistent individual differences in inter‐annual spatial distribution and habitat occupied throughout the non‐breeding period using a large geolocator tracking dataset of 729 adult seabirds breeding at 13 colonies across the Northeast Atlantic and repeatedly tracked up to 7 years over a 9‐year period. Additionally, we used a similarity index to calculate relative fidelity to either geographical sites or habitats and linear mixed‐effects models to assess persistence of spatial site fidelity over multiple years. Results Both guillemot species exhibited IMSF across a large part of the genus’ range which persisted over multiple years. Individuals of both species and almost all colonies showed fidelity to geographical sites and not to specific habitats. Main conclusions Guillemots show IMSF that is best explained by site familiarity (fidelity to specific sites) rather than habitat specialization (fidelity to specific habitats). In the context of rapidly changing environments, favourable habitats may permanently shift locations and hence species displaying IMSF driven by site familiarity—such as the genus Uria —may not be able to adjust their migration strategies sufficiently fast to sustain individual fitness and ensure population persistence.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Marine biology of the pacific lamprey Entosphenus tridentatus - Benjamin J. Clemens; Laurie Weitkamp; Kevin Siwicke; Joy Wade; Julianne Harris; Jon Hess; Laurie Porter; Keith Parker; Trent Sutton; Alexei M. Orlov (Reviews in Fish Biology and Fisheries, 2019)

Prolonged standing increases lower limb arterial stiffness - Aaron R. Caldwell; Kaitlin M. Gallagher; Benjamin T. Harris; Megan E. Rosa-Caldwell; Marcus Payne; Bryce Daniels; Matthew S. Ganio (European Journal of Applied Physiology, 2018)

Petrogenesis of low-δ18O quartz porphyry dykes, Koegel Fontein complex, South Africa - Chris Harris; Kwenidyn Mulder; Saheli Sarkar; Benjamin Whitehead; Sherissa Roopnarain (Contributions to Mineralogy and Petrology, 2018)

Spatial-temporal variations in surface ozone over Ushuaia and the Antarctic region: observations from in situ measurements, satellite data, and global models - Mohd Shahrul Mohd Nadzir; Matthew J. Ashfold; Md Firoz Khan; Andrew D. Robinson; Conor Bolas; Mohd Talib Latif; Benjamin M. Wallis; Mohammed Iqbal Mead; Haris Hafizal Abdul Hamid; Neil R. P. Harris; Zamzam Tuah Ahmad Ramly; Goh Thian Lai; et al. (Environmental Science and Pollution Research, 2018)

Translations of volcanological terms: cross-cultural standards for teaching, communication, and reporting - Andrew J. L. Harris; Alexander Belousov; Sonia Calvari; Hugo Delgado-Granados; Matthias Hort; Ken Koga; Estuning Tyas Wulan Mei; Agung Harijoko; José Pacheco; Jean-Marie Prival; Carmen Solana; Þorvaldur Þórðarson; et al. (Bulletin of Volcanology, 2017)

The longevity of para-aminopropiophenone (PAPP) wild dog baits and the implications for effective and safe baiting campaigns - Matthew Gentle; James Speed; Benjamin L. Allen; Stacy Harris; Hellen Haapakoski; Kerry Bell (Environmental Science and Pollution Research, 2017)

Eruption and emplacement dynamics of a thick trachytic lava flow of the Sancy volcano (France) - Benjamin Latutrie; Andrew Harris; Etienne Médard; Lucia Gurioli (Bulletin of Volcanology, 2017)

Preliminary differences in peripheral immune markers and brain metabolites between fatigued and non-fatigued breast cancer survivors: a pilot study - Suzanna Maria Zick; Heather Zwickey; Lisa Wood; Bradley Foerster; Tohfa Khabir; Benjamin Wright; Eric Ichesco; Ananda Sen; Richard Edmund Harris (Brain Imaging and Behavior, 2014)

Aflatoxin contamination in food commodities in Bangladesh - Monika Roy; Julie Harris; Sadia Afreen; Eszter Deak; Lalitha Gade; S. Arunmozhi Balajee; Benjamin Park; Tom Chiller; Stephen Luby (Food Additives & Contaminants Part B-Surveillance, 2013)

Confidence of primary care physicians in their ability to carry out basic medical genetic tasks—a European survey in five countries—Part 1 - Irmgard Nippert; Hilary J. Harris; Claire Julian-Reynier; Ulf Kristoffersson; Leo P. ten Kate; Elizabeth Anionwu; Caroline Benjamin; Kirsty Challen; Jörg Schmidtke; R. Peter Nippert; Rodney Harris (Journal of Community Genetics, 2011)

General practitioner management of genetic aspects of a cardiac disease: a scenario-based study to anticipate providers’ practices - Kirsty Challen; Hilary Harris; Ulf Kristoffersson; Irmgard Nippert; Joerg Schmidtke; Leo P. Ten Kate; Caroline Benjamin; Elizabeth Anionwu; Anne-Marie Plass; Claire Julian-Reynier; Rodney Harris (Journal of Community Genetics, 2010)

The GPSTk: an open source GPS toolkit - R. Benjamin Harris; Richard G. Mach (GPS Solutions, 2007)

Differential sectoriality in long-distance transport in temperate tree species: evidence from dye flow, 15N transport, and vessel element pitting - Colin M. Orians; Margret M. I. van Vuuren; Nancy L. Harris; Benjamin A. Babst; George S. Ellmore (Trees, 2004)

Comparison of recent coral life and death assemblages to pleistocene reef communities: Implications for rapid faunal replacement on recent reefs - Benjamin J. Greenstein; Lora A. Harris; H. Allen Curran (Carbonates and Evaporites, 1998)